Kiai Shaleh Darat’s Moderate Sufism: Dialectic of Submission, Sincerity and World Affairs in Haża Al-Kitab Matnu Al-Ḥikam - Akhmad Luthfi Aziz (Jurnal Penelitian, 2019)
Kiai Shaleh Darat is considered as a scholar who has a diversity of scientific disciplines. In contemporary Sufistic studies of the Archipelago (Indonesia), he has not obtained a decent place as in the study of Azra (2007), Mulyati (2006), Anwar and Shalihin (2006). Nevertheless, the sufistic side of the teachings of the Kiai Muhammad Shaleh al-Samarani looks very striking in each of his works. This study seeks to analyze the mysticism of the Kiai Shaleh Darat in the book Haża Al-Kitab Matnu Al-Ḥikam. Through qualitative methods, the research data comes from literature review. This study succeeded in uncovering Sufism developed by the Kiai Shaleh Darman with tasawuf akhlaqi (sunni-amali), in which not only contains Sufism teachings which emphasize the basic concept of Islam, namely the submission of a servant to his God, but also the path of humanity. The narrative of divinity and humanity merges into Sufism. Kiai Shaleh lied between traditionalism and modernity, locality and globalism. This characteristic is reflected in the discourse that was rolled out: submission, illiteracy, world problems, nationalism, hard work, and clothing models intersecting as a path to God.